Case Study of the Effect of Stratigraphic Location on Roof Stability in Rock Salt - Chris T. Franke (International Conference on Ground Control in Mining, 1997)
The Waste Isolation Pilot Plant is a deep underground facility mined in bedded salt interspersed with persistent clay inter- beds. The clay seams delineate beams of salt above and below the excavations which strongly influence excavation performance. This paper reviews available rock mechanics information relevant to improving drift stability by removing the roof beam. Conceptual deformation mechanisms, relevant field data, and numerical analyses were used to investigate the effects of mining the roof of the excavations along a clay seam. Finally, a case study that applies the results of this investigation is presented.